Og Gud sagde til Abraham - Davidsen, Ole (Religionsvidenskabeligt Tidsskrift, 1995)
Covenant, circumcision and sacrifice in the Abraham story are analysed, especially as articulated in the raltionship between God, Abraham and Isaac. Two texts are particularly in focus, Gen and17 Gen 22:1-19, concerning the initiation of Abraham as covenantal servant, the covenant as a series of events related to a reciprocal structure of exchange, and the connection between initiation, circumcision and sacrifice. The stories of P and JE about the miraculous birth of Isaac are almost the same, but differ on a certain point. Where P recounts the circumcision of Isaac, JE tells the story about his sacrifice, and it is shown how the sacrificial narrative functions as the basic myth for an understanding of circumcision. Introducing the jewish Aqedah-tradition and tis connections with the understanding of the death of Jesus in New Testament, it is demonstrated how the relationship between sacrifice and circumcision in the Abraham story in a displaced manner is repeated in the relationship between sacrifice and baptism in the Jesus story.